Intraorganizational Mobility in Russian Enterprises: Dynamics of Structural and Normative Regulators of Careers - Мария Александровна Бурлуцкая (Journal of Economic Sociology, 2011)
The paper is devoted to the intraorganizational mobility at the Russian industrial plants (1990–2000). Author investigates direction and intensity of mobility as well as structural and normative factors regulating job careers. Based on several case-study, the paper demonstrates that in conditions of Russia structural changes encourage intraorganizational mobility. As for normative regulators as an element of corporate culture, they significantly vary among enterprises.